EASiCard Encryptor of audio streams on smart cards - Cantillas, Joan Lotus T.
The impetus for the work presented in this paper arose from the need to enable secure audio delivery and protection of digitized music or speech against eavesdropping, illegal use, reproduction and distribution of electronic and audio media. To protect multimedia content, encryption is often used to limit access to authorized users. In this paper, a Low-Complexity Partial-Encryption scheme that provides protection for widely-accepted, WAVE audio encoding format is presented. Encryption techniques will be apples on both recorded media and streamed audio media. The aim is to provide the listeners a partially encrypted audio material, produced through the existing cipher portfolios found at the eStream project (http://www.ecrypt.eu.org/stream/), that can be upgraded to full-quality audio file by simply acquiring a key and a pseudo-random number issued in an authentication protocol, nonce. The implementation, also, of the audio stream frequency-based selective partial encryption is instigated on Smart Cards through javacard programming.